2009
DOI: 10.1167/iovs.08-2417
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Effector T Cells in Dry Eye Disease

Abstract: Purpose Dry eye disease (DED) is associated with ocular surface inflammation that is thought to be primarily mediated by CD4 T cells. The purpose of this study was to investigate whether this T cell mediated immune response is generated in the lymphoid compartment, and to characterize the functional phenotype of the T cells activated in DED. Methods DED was induced in female C57BL/6 mice by exposure to a desiccating environment in the controlled environment chamber (CEC) and to systemic scopolamine. T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
114
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 39 publications
2
114
0
Order By: Relevance
“…A majority of the experimental studies investigating the immunopathogenesis of DED have used a combination of desiccating environmental stress (e.g., CEC) and pharmacologic tear inhibition (e.g., SCP) to induce murine DED. [4][5][6][7][8][9] A previous study showed that SCP not only reduced lacrimal secretion, but induced lacrimal gland inflammation. 24 Given the potential effects of SCP on immune responses, it is vital to determine the effects of mAChR blockade on pathogenic immune responses in this model of experimental DED.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A majority of the experimental studies investigating the immunopathogenesis of DED have used a combination of desiccating environmental stress (e.g., CEC) and pharmacologic tear inhibition (e.g., SCP) to induce murine DED. [4][5][6][7][8][9] A previous study showed that SCP not only reduced lacrimal secretion, but induced lacrimal gland inflammation. 24 Given the potential effects of SCP on immune responses, it is vital to determine the effects of mAChR blockade on pathogenic immune responses in this model of experimental DED.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies that combined desiccating stress (e.g., CEC) and SCP-induced DED. [5][6][7] However, immune responses in the draining CLN of CEC and SCP-induced models differ (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After activation, Th cells can differentiate into Th-1, Th-2, Th-3, and Th-17 subtypes. Studies have shown that Th-1 and Th-17 cells are correlated with the pathogenesis of dry eye (Stern et al, 2005;Yoon et al, 2007;De Paiva et al, 2009;El Annan et al, 2009;Zheng et al, 2010).…”
Section: Discussionmentioning
confidence: 99%